Coordination: the key to governing the water-land-food nexus in Zambia? - Waltina Scheumann; George Phiri (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Water- and land-related resource conflicts are the starting point of the Zambian nexus study. Zambia is endowed with abundant land and water resources, the utilisation of which offers huge potential for the country's economic development. For this reason, the Zambian Government has planned the gradual expansion of irrigated areas throughout the country to boost agricultural production and productivity to meet domestic food demands, to supply regional and international markets, and to create income and employment for smallholders and the rural population. However, changing land use from rain-fed to irrigation on a large scale fuels competition among water users. But conflicts are not only about water: The expansion takes place in areas under customary land tenure, generating conflicts between commercial investors and pre-existing smallholders, and between local people and the chiefs administering the land. In order to realise the government's vision of sustainable development in all its dimensions (economic, social and environmental), good governance and effective coordination is required. Coordination, which carries the positive connotation of “good governance”, seems to be the way out of silo planning and uncoordinated implementation. But coordination is not automatically forthcoming, nor is it easy to initiate and sustain. The study analyses the modes at hand to coordinate activities of more or less independent public-sector units related to agricultural development activities, the kind of coordination problems and the barriers and hindrances to effective coordination. The focus of the study is the planning and licensing process of large-scale public-private agricultural investment projects with water/irrigation infrastructure as major components. The Zambia study argues that cross-sectoral coordination is not the only governance issue to be solved to minimise resource-related conflicts and their environmental and social impacts. The study shows that governing the water-land-food nexus is not only a cross-sectoral coordination issue (horizontal coordination) but also an issue of effective vertical coordination. This is most evident regarding land issues. This governance issue originates from the plurality and concurrency of traditional and modern land-tenure systems. Effective implementation of the Zambian government's policy and strategy is also as much an issue of assigning distinct functions to public sectors units and equipping them with sufficient resources for implementation; of upgrading public units to fully fledged administrative units and of considering viable financial models for the water authority WARMA. We applied the Network of Adjacent Action Situations (NAAP) concept that allows one to analyse complex policy settings and to specifically take account of the many decision-making public units that steer the Zambian water-land based agricultural development strategy.
Keywords: 330; Agenda 2030; Governance